2016
DOI: 10.1007/s13181-016-0564-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Emergency Department Resource Utilization for Poisoning-Related Visits, 2003–2011

Abstract: In recent years, there has been an increase in poisoning-related emergency department (ED) visits. This study examines trends in ED resource utilization for poisoning-related visits over time. A retrospective review of data from the National Hospital Ambulatory Medical Care Survey, 2003-2011, was conducted. All ED visits with a reason for visit or ICD-9 code related to poisoning were included. We examined the number of ED visits and resources used including diagnostic studies and procedures performed, medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Our findings have important implication from a public health standpoint. Poisoning remains a leading cause of preventable injuries in childhood and adolescence 1 , whose treatment involves a huge cost of economic and human resources 51 , 52 . The present meta-analysis has shown that children and adolescents with ADHD are a population with an increased risk of poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have important implication from a public health standpoint. Poisoning remains a leading cause of preventable injuries in childhood and adolescence 1 , whose treatment involves a huge cost of economic and human resources 51 , 52 . The present meta-analysis has shown that children and adolescents with ADHD are a population with an increased risk of poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increases in fatal opioid overdoses, EDs have witnessed substantial increases in visits for non-fatal opioid overdoses 12–14. About 120 000 ED visits were reported for suspected non-fatal opioid overdoses between July 2016 and September 2017 in 16 states participating in the Enhanced State Opioid Overdose Surveillance, representing a 35% increase over this period 15.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nationally collated ICD-10 coded data in the UK means that the true burden of ARDT-related health care utilisation is not understood [ 1 – 6 ]. However, there have been no studies to determine whether these issues are only representative of the UK, or whether this also occurs in other European healthcare systems.…”
Section: Introductionmentioning
confidence: 99%